The growth of companies as a function of total assets (2018)
Total Assets determines the size of the companies and allows classifying them by economic relevance in every industry. However, the path of company growth, measured by Total Assets, might be different depending on the type of industry and the size of companies. Accordingly, this research focuses on identifying the trend in Total Assets growth across industries and company size by finding a function that fits industries-company-size combinations. The method is analytical, deductive and empirical; it is a cross-sectional analysis with six industries in two years (three for every year) with four different company sizes, based on Total Assets, grouped into the categories of micro, small, medium or big companies, for a total of 24 industry-company-size-year combinations. Every combination of industry-company-size is analyzed to see which function yields the best fit. The functions are: 1) Linear, 2) Logarithmic, 3) Inverse, 4) Quadratic, 5) Cubic, 6) Compound, 7) Power, 8) S, 9) Growth, 10) Exponential, and 11) Logistic. The test consists of statistical regression analysis, ANOVA significance test and explained variance. The cubic function gives the best results in all industry-company-size combination for the two years. Other functions are relevant in some, but not all, combinations of categories. The conclusion is that cubic function provides the best fit for Total Assets company growth across industry-company-size combinations for the two years. Cubic function properties are described for future applications. © 2018, World Scientific and Engineering Academy and Society. All rights reserved.